IgG4 donor‐specific HLA antibody profile is associated with subclinical rejection in stable pediatric liver recipients. Issue 2 (1st November 2019) - Jackson, Annette M.; Kanaparthi, Sai; Burrell, Bryna E.; Lucas, Donna P.; Vega, Renato M.; Demetris, Anthony J.; Feng, Sandy
Abstract : The impact of donor‐specific HLA antibody (DSA) following liver transplantation remains controversial. We hypothesized DSA IgG subclass characteristics, compared to total DSA IgG, might correlate with specific histopathological phenotype(s) of subclinical graft injury. We therefore studied 129 stable, arguably "clinically ideal, " pediatric liver recipients at the time of a screening biopsy to enter an immunosuppression withdrawal trial. Sixty‐five (50%) subjects tested positive for class II DSA. IgG subclass profile was characterized by mean fluorescence intensity (MFI) and normalized subclass composition (>5%). A prominent IgG4 DSA profile was strongly correlated with greater HLA mismatch, a histopathological phenotype characterized by the presence of interface activity (with variable degrees of fibrosis), and a transcriptional profile of attenuated T cell–mediated rejection. Specifically, compared to those without class II DSA, those with IgG4 class II DSA MFI sum >2000 exhibited an odds ratio (OR) of 20.79 (95% confidence interval [CI] 4.38‐98.69) and IgG4 subclass composition >5% exhibited an OR of 8.99 (95% CI 2.70‐29.9). Our data suggest that IgG4 DSA may serve as a useful biomarker to identify, among clinically and biochemically stable liver transplant recipients, a subset with histological and transcriptional features indicative of an active, suboptimally controlled alloimmune response. Abstract : Among stable pediatric liver recipients, a prominent IgG4 donor‐specific antibody profile may serve as a biomarker to identify suboptimally controlled alloimmune responses, and correlates with greater HLA mismatch, a transcriptional profile of attenuated T cell–mediated rejection, and a histopathological phenotype of interface activity.